2016
DOI: 10.1002/bab.1319
|View full text |Cite
|
Sign up to set email alerts
|

Forxiga (dapagliflozin): Plausible role in the treatment of diabetes‐associated neurological disorders

Abstract: Numerous clinical and epidemiological studies have provided direct evidence to strengthen the link between type 2 diabetes (T2D) and Alzheimer's disease (AD). The possibility that T2D patients might be at increased risk in developing AD has serious societal implications. Sodium glucose co-transporter 2 (SGLT2) is one of the best targets in the treatment of diabetes, whereas acetylcholinesterase (AChE) has long been regarded as a therapeutic target for AD. This study explores the molecular interactions between … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
42
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 57 publications
(43 citation statements)
references
References 37 publications
(37 reference statements)
1
42
0
Order By: Relevance
“…In this animal model, improvement in the MWM is attributed to the inhibition of acetylcholinesterase activity and monoamine levels in the brain. Canagliflozin might act as a dual acetylcholinesterase and SGLT2i [55], supporting a dual role for SGLT2i at the central level [56,57] and opening an interesting venue, since acetylcholinesterase inhibitors, and NMDA receptor antagonist memantine, are the only FDAapproved options to treat AD. In our learning and memory studies, we additionally used a very demanding version of the NOD task, which allows the assessment of episodic memory [58].…”
Section: Discussionmentioning
confidence: 96%
“…In this animal model, improvement in the MWM is attributed to the inhibition of acetylcholinesterase activity and monoamine levels in the brain. Canagliflozin might act as a dual acetylcholinesterase and SGLT2i [55], supporting a dual role for SGLT2i at the central level [56,57] and opening an interesting venue, since acetylcholinesterase inhibitors, and NMDA receptor antagonist memantine, are the only FDAapproved options to treat AD. In our learning and memory studies, we additionally used a very demanding version of the NOD task, which allows the assessment of episodic memory [58].…”
Section: Discussionmentioning
confidence: 96%
“…7 The effects of SGLT2-Is on AD progression have not yet been studied, 5 although certain drugs (i.e., dapagliflozin and canagliflozin) might act as potent dual inhibitors of SGLT2 and acetylcholinesterase (AChE), implying that SGLT2-Is may have some therapeutic potential for DM-associated AD. 9,10 SGLT2/SLC5A2 protein is reported to be exclusively expressed on the brush border membrane (BBM) of proximal tubular epithelial (PTE) cells in the kidney. 11,12 Notably, Bonner et al (2005) reported SGLT2/SLC5A2 expression in the α cells of the human pancreatic islets.…”
Section: Introductionmentioning
confidence: 99%
“…SGLT1s are expressed and are functional in regions of cerebellum, hippocampus, frontal cortex, putamen, amygdala, nucleus caudatus, parietal cortex, and paraventricular nucleus of the hypothalamus in rats . In addition, molecular docking studies demonstrate that SGLT2I may interact and inhibit acetylcholinesterase, which is a primary target for AD treatment . Whether SGLT2Is can cross the blood‐brain barrier and act in the brain remains unclear.…”
Section: Introductionmentioning
confidence: 99%